2022
DOI: 10.1007/s41348-021-00526-y
|View full text |Cite
|
Sign up to set email alerts
|

Vector transmission and epidemiology of ‘Candidatus Phytoplasma pyri’ in Austria and identification of Cacopsylla pyrisuga as new pathogen vector

Abstract: Pear decline, induced by the phytoplasma 'Candidatus Phytoplasma pyri', transmitted by pear psyllids, is one of the most devastating diseases on Pyrus communis in Europe and North America. Investigations of pear psyllids in 4 pear orchards in lower Austria showed the presence of Cacopsylla pyri, C. pyricola and C. pyrisuga at all locations. PCR analyses revealed overall phytoplasma infection rates for C. pyri of 5.4%, for C. pyricola, of 4.6%, for C. pyrisuga remigrants of 9.6% and for C. pyrisuga emigrants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These psylla species are also vectors of some typical pear tree pathogens (Moreno et al, 2021) such as the bacterium Erwinia amylovora Burrill, which causes fire blight (Hildebrand et al, 2000), one of the most devastating pear diseases (Sestras et al, 2008). It has also been confirmed that the pear psyllid is the vector transmitting the phytoplasma known as 'Candidatus Phytoplasma pyri' that causes a serious disease known as 'pear decline' (Tešanović et al, 2016;Riedle-Bauer et al, 2022).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 97%
“…These psylla species are also vectors of some typical pear tree pathogens (Moreno et al, 2021) such as the bacterium Erwinia amylovora Burrill, which causes fire blight (Hildebrand et al, 2000), one of the most devastating pear diseases (Sestras et al, 2008). It has also been confirmed that the pear psyllid is the vector transmitting the phytoplasma known as 'Candidatus Phytoplasma pyri' that causes a serious disease known as 'pear decline' (Tešanović et al, 2016;Riedle-Bauer et al, 2022).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 97%
“…However, it has been recently confirmed as a vector of " Ca. Phytoplasma pyri ", the causing agent of Pear Decline ( Riedle-Bauer et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…C. pyrisuga had not been considered a competent vector of ‘ Ca . Phytoplasma mali’ (Jarausch et al, 2019 ; Jarausch & Jarausch, 2010 ), until Riedle‐Bauer et al ( 2022 ) recently demonstrated experimentally that remigrants of C. pyrisuga are able to transmit ‘ Ca . Phytoplasma mali’ to pear trees in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…Both vectors produce up to 3–5 generations per year and show resistance to insecticides, making it difficult to control population outbreaks (Civolani, 2012 ). In contrast to C. pyri and C. pyricola , C. pyrisuga had been considered a non‐vector species until recently, when its vector competence was experimentally proven in Austria (Riedle‐Bauer et al, 2022 ). However, it is not known to what extent this species acts as a vector in other parts of Europe.…”
Section: Introductionmentioning
confidence: 99%